The Occurrence of Lung Cancer and Non-Pulmonary Malignancies After Pleural Infections. (March 2021) - Khan, J.; Ala-Seppälä, H.; Lehtomäki, A.; Toikkanen, V.; Pohja, E.; Laurikka, J.; Ukkonen, M.
Background and Aims: Patients who develop infections of the pleura have several risk factors for malignancies, particularly lung cancer, and the infections might even be caused by undiagnosed intra-thoracic neoplasms. The aim of the study was to compare the occurrence of lung cancer and other malignancies between patients treated for pleural infections and controls during long-term follow-up. Materials and Methods: All consecutive patients treated for pleural infections between January 2000 and June 2016 at the Tampere University Hospital were included. Ten matched controls and data regarding later cancer diagnoses were requested from national registries. The cancer types and rates, the diagnostic delays, as well as survival were compared between patients and controls. Results: The material comprised 506 patients and 5022 controls (78% was male and median age was 60 years in both groups) with a median follow-up time of 69 months. In total, 74% of pleural infections were related to pneumonia. The occurrence of lung cancer during follow-up was 3.0% in all patients, 2.2% in pneumonia-related cases, and 0.6% in controls, p < 0.001 when compared with controls. The overall rate of non-pulmonary malignancies did not differ. Lung cancer was diagnosed within 3 months in 73% of patients versus in 6.9% of controls, p < 0.001. The survival in patients with later lung cancers or other malignancies was inferior to that of controls with similar neoplasms. Conclusion: The rate of lung cancer diagnoses was significantly increased in patients treated for pleural infections when compared with matched controls and the prognosis of patients with subsequent malignancies was impacted.